Egzegeza Księgi Izajasza 61,1-11: historia redakcji i pytanie o tożsamość proroka zwanego Tritoizajaszem - Slawik, Jakub (Collectanea Theologica, 2019)
Exegesis of Is 61 has shown that the chapter is a literal composition, which consists of two parts: a frame vv. 1-3+10-11 and a middle part vv. 4-9. The two framing sections, vv.1-3(10-11) could first have been a separate text. V. 3aa is possibly a secondary addition, which joins chapter 61 with chapters 60 and 62. But it is reasonable to read and interpret Is 61 as one unit, in which a prophetic „I” take the floor. The „I” poses as a servant known from Deutero-Isaiah’s Songs of JHWH’s Servant. But in this „I” we hear tradents who passed down and updated Deutero-Isaiah’s tradition, and added new God’s promises. The prophet Trito-Isaiah, who should be like the other prophets speaking to the people, never existed. However the tradents understood their mission as prophetical one.